Merajut Industri Kreatif di Panti Asuhan Mawaddah Warohmah melalui Pelatihan Seni Patchwork dan Lace - Yekti Sri Rahayu; Erna Atiwi Jaya Esti (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2021)
Mawaddah Warohmah Orphanage Malang City is the social service institutions that accommodates orphans and poor people from various regions. The skill development of the productive age orphanage children has not been maximally obtained. This program aims to improve the skills of orphans and poor people under the guidance of the orphanage through the development of creative industries that have the opportunity to become home-scale businesses. The group participation approach method in this program involves orphans and poor people under the guidance of the Orphanage actively in training and mentoring for creative classes